Lima: Chronicle of a Deterioration - Flores Galindo, Alberto (1985)
Discussion about the city of Lima, from the historical reflections of César Pacheco Vélez, author of the book "Memoria y Utopía de la Vieja Lima" (Memory and Utopia of Old Lima).